THE RIGHT OF DIVULGATION AS A FORM OF THE RIGHT TO PRIVACY - Anika Kovacevic; Nikola Milosavljevic (Pravo)
The author’s personal right of divulgation—the right to publish a work—is not universally recognized in all countries. Considering its potential significance for the author, it is necessary to examine the rationale behind its legal regulation. To that end, in the first part of the paper, the authors, applying legal dogmatic and sociological methods, analyze the right to privacy, its legal foundations, and its various forms. In the second part, using the legal dogmatic method, they examine the concept and scope of the right of divulgation and conduct a comparative legal analysis. By applying deductive and comparative methods, the authors further explore potential legal grounds for the recognition of the right of divulgation, particularly its relationship with the right to privacy. Based on this analysis, the authors conclude that the right of divulgation can be viewed as a form of the right to privacy, thereby highlighting the need for its broader international recognition in order to protect the author’s privacy interests.